The ECLAC model in the Socialism of the 21st Century in Ecuador (2021)
The industrialization models of ECLAC, developed during the 1950s, 1960s and 1970s, and those of Ecuador, implemented by the 21st-century socialist government, are similar in their attempt to industrialize through the substitution of imports and government expenditure. In both cases, the economic policies focused on a closed economy, with high tariff barriers, and a strong role of the state as the main actor in the economy. The article uses a comparative method of analysiswhich emphasizes the outcomes of both of the periods studied. The results show that the models applied brought the same problems; imbalance in external trade and rising public debt. An alternative premise is suggested, that the models applied are the main causes of the debt crisis in the 1980s and the increasing public debt in the government of Rafael Correa.